Trichostatin A suppresses hearing loss by reducing oxidative stress and inflammation in an Alport syndrome model. - Yoon Seok Nam; Eun-Ji Gi; Yoo-Seung Ko; Sungsu Lee; Hyong-Ho Cho (PLoS ONE)
Alport syndrome (AS) is a genetic disorder marked by mutations in type IV collagen, leading to kidney glomerular dysfunction. AS also involves the cochlea, causing late-onset progressive hearing loss. Currently, there are no therapeutic drugs to protect hearing from AS. HDAC inhibitors (HDACis) are chemical compounds that block the activity of histone deacetylase and are known to exert diverse biologic effects. We investigated the effect of Trichostatin A (TSA), an HDACi, to assess its potential to inhibit hearing deterioration in AS. Col4a3 knockout (KO) mice were treated with TSA at 3 weeks of age, and hearing levels were measured using auditory brainstem response (ABR). The results demonstrate that TSA significantly protects the hearing of KO mice compared to the untreated group. The TSA-treated group exhibited a reduction in the levels of oxidative stress markers 4-Hydroxynonenal and 3-Nitrotyrosine, along with a decrease in inflammatory cytokines, in both the mouse cochlea and in vitro HEI-OC1 (House Ear Institute-Organ of Corti 1) cell and HEK (Human Embryonic Kidney)293T cells. AS demonstrated a thickening in the stria vascular vessels, a phenomenon that TSA attenuated. Col4α3 deficiency showed down-regulation of Hemeoxygenase-1 (HO-1), a key anti-inflammatory molecule. TSA treatment induced HO-1 signaling, which contributed to the inhibition of oxidative stress and inflammatory cytokines. These findings suggest that TSA represents a promising candidate molecule for mitigating the progression of hearing loss in AS.